2021
DOI: 10.1002/jcp.30456
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dimethyl itaconate against fibroblast–myofibroblast differentiation during pulmonary fibrosis by inhibiting TXNIP

Abstract: Fibroblast-myofibroblast differentiation (FMD) is a critical cellular phenotype during the occurrence and deterioration of pulmonary fibrosis (PF). FMD can increase with an elevated level of reactive oxygen species (ROS) on fibroblasts under oxidative stress. Thioredoxin-interacting protein (TXNIP) is an α-arrestin family protein that regulates the level of intracellular ROS. Nuclear factor erythroid 2-related factor 2 (Nrf2) can protect against FMD in PF. However, the relationship between Nrf2 and TXNIP in FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Nrf2 balances not only oxidative stress but also has negative effects on TGF-β1-mediated profibrotic signal transduction [14,15]. Previous studies have shown that Nrf2 plays an important role in preventing lung inflammation and fibrosis [16,17]. These results indicate that strategies targeting Nrf2 have antipulmonary fibrosis potential.…”
Section: Introductionmentioning
confidence: 91%
“…Nrf2 balances not only oxidative stress but also has negative effects on TGF-β1-mediated profibrotic signal transduction [14,15]. Previous studies have shown that Nrf2 plays an important role in preventing lung inflammation and fibrosis [16,17]. These results indicate that strategies targeting Nrf2 have antipulmonary fibrosis potential.…”
Section: Introductionmentioning
confidence: 91%
“…TGF-β1 has been identified as a major pro-fibrogenic cytokine in IPF patients and can be produced by a variety of cells, such as alveolar macrophages, alveolar epithelial cells, and myofibroblasts [ 139 , 140 ]. Recently, a growing number of studies have suggested that fibroblast–myofibroblast differentiation (FMD) is a critical cellular phenotype during the occurrence and deterioration of PF [ 141 , 142 , 143 ]. FMD can increase with an elevated level of ROS in fibroblasts under oxidative stress.…”
Section: Nrf2 and Fibroblasts In Pulmonary Fibrosis—tgf-β1/smad Pathwaymentioning
confidence: 99%
“…Compared with Nrf2 knockdown, Nrf2 activation increased antioxidant capacity and myofibroblast dedifferentiation in IPF fibroblasts [ 147 ]. The activation of Nrf2 by dimethyl itaconate 13 can protect against TGF-β1-induced FMD via the ROS/TXNIP signaling pathway and inhibit TXNIP-mediated FMD in PF [ 141 ]. Tanshinone IIA inhibited myofibroblast activation, rebalanced Nrf2-NOX4, and limited glutaminolysis in myofibroblast proliferation by activating the Nrf2/GSH signaling pathway [ 63 ].…”
Section: Nrf2 and Fibroblasts In Pulmonary Fibrosis—tgf-β1/smad Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 balances not only oxidative stress but also has negative effects on TGF- β 1-mediated profibrotic signal transduction [ 14 , 15 ]. Previous studies have shown that Nrf2 plays an important role in preventing lung inflammation and fibrosis [ 16 , 17 ]. These results indicate that strategies targeting Nrf2 have antipulmonary fibrosis potential.…”
Section: Introductionmentioning
confidence: 99%